2021
DOI: 10.1038/s41597-021-00955-2
|View full text |Cite
|
Sign up to set email alerts
|

A sub-national real-time epidemiological and vaccination database for the COVID-19 pandemic in Canada

Abstract: The COVID-19 pandemic has demonstrated the need for real-time, open-access epidemiological information to inform public health decision-making and outbreak control efforts. In Canada, authority for healthcare delivery primarily lies at the provincial and territorial level; however, at the outset of the pandemic no definitive pan-Canadian COVID-19 datasets were available. The COVID-19 Canada Open Data Working Group was created to fill this crucial data gap. As a team of volunteer contributors, we collect daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…A higher value for the stringency index indicates greater stringency of public health measures. The 7-day rolling average of incident cases of COVID-19 per 100,000 population by province was extracted from the Canada Open Data Working Group datasets ( Berry et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…A higher value for the stringency index indicates greater stringency of public health measures. The 7-day rolling average of incident cases of COVID-19 per 100,000 population by province was extracted from the Canada Open Data Working Group datasets ( Berry et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Our analysis combines data from multiple sources (summarized in Table 1) including the Public Health Agency of Canada (PHAC), and the Newfoundland and Labrador Centre for Health Information (NLCHI). A data source for travel-related cases was the COVID-19 Canada Open Data Working Group (CCODWG) (Berry et al, 2020, 2021), a group of volunteers who curated data from government and non-government sources. We validated the CCODWG data with travel-related cases as reported by the NL and NB provincial governments and found that the CCODWG data accurately describes the number of travel-related cases in NL and NB (Figure S1).…”
Section: Methodsmentioning
confidence: 99%
“…Organization (WHO) [27] COVID-19 Canada Open Data Working Group [28], [29] This is an epidemiological data from the COVID-19 Epidemic in Canada.…”
Section: World Healthmentioning
confidence: 99%